Crystal structure of methyl ((4-aminobenzyl)sulfonyl)-L-prolinate, C13H18N2O4S - Wang Zhen; Zhao Feng-Lan; Hou Gui-Ge; Meng Qing-Guo (Zeitschrift für Kristallographie - New Crystal Structures)
C13H18N2O4S, orthorhombic, P212121 (no. 19), a = 6.8619(2) Å, b = 12.0735(4) Å, c = 16.6591(5) Å, V = 1380.16(7) Å3, Z = 4, R gt(F) = 0.0236, wR ref(F 2) = 0.0604, T = 150 K.